Patient Admission Patterns and Acquisitions of "Feeder" Hospitals - Sayaka Nakamura; Cory Capps; David Dranove (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
Large, urban tertiary care hospitals often acquire outlying community hospitals. One possible motivation is to increase referrals. Sophisticated acquirers may even attempt to concentrate additional referrals among more profitable patients. We explore these issues by studying 26 vertical acquisitions in Florida and New York that occurred in the late 1990s, a peak period for such transactions. We compare changes in referrals of patients from target market areas to changes in a matched set of control markets. We find that roughly 30 percent of the vertical acquisitions resulted in a significant increase in referrals to the acquirer. Very few acquisitions were followed by decreases in referrals. When acquisitions did lead to increased referrals, the effect was usually largest for patients with more remunerative insurance and patients undergoing more profitable procedures. However, we find no evidence that hospitals selectively avoided referrals of patients with severe conditions for which costs might exceed reimbursements.
Keywords: 330; Hospitals; Mergers and Acquisitions; Referrals; Patient Selection